Factors affecting customer satisfaction in mobile telecommunication industry in Bangladesh - Rahman, Md. Hasebur (Business, Management and Economics Engineering, 2014)
Identification of factors responsible for customer satisfaction is a key concern of marketing scholars and marketers in now a days and it will remain in the future. There is considerable evidence that quality factors affecting customer satisfaction in numerous ways. However, this empirical study is initiated to find out what particular factors responsible for customer satisfaction in the mobile telecommunication industry in Bangladesh. 282 samples have been collected through structured questionnaire; study reveals that service innovativeness, service reliability, service competitiveness and service consistency have significant influence on making customer satisfied and the operator’s network/signal coverage, pricing, offering, fulfillment of customer demand, value added service, brand value and operators contribution for society have insignificant influences on making customer satisfied at five percent level of significant at multiple regression analysis. On the basis of these findings; study concludes that in promoting customer satisfaction mobile service providers should be concerned for factors responsible for insignificant influence on customer satisfaction and care of those factors have significant influence on promoting customer satisfaction in telecommunication industry in Bangladesh.